Genetic determinants of plasma β2‐glycoprotein I levels: a genome‐wide association study in extended pedigrees from Spain. Issue 3 (13th March 2013) - Athanasiadis, G.; Sabater‐Lleal, M.; Buil, A.; Souto, J. C.; Borrell, M.; Lathrop, M.; Watkins, H.; Almasy, L.; Hamsten, A.; Soria, J. M.
Summary Background β2‐Glycoprotein I (β2‐GPI), also designated apolipoprotein H, is a 50‐kDa protein that circulates in blood at high concentrations, playing important roles in autoimmune diseases, hemostasis, atherogenesis, and angiogenesis, as well as in host defense against bacteria and in protein/cellular waste removal. Plasma β2‐GPI levels have a significant genetic component (heritability of 80%). Objectives To present the results of a genome‐wide association study for plasma β2‐GPI levels in a set of extended pedigrees from the Genetic Analysis of Idiopathic Thrombophilia (GAIT) Project. Patients/Methods A total of 306 individuals for whom β2‐GPI plasma measurements were available were typed for 307 984 single‐nucleotide polymorphisms (SNPs) with the Infinium 317k Beadchip (Illumina). Association with the β2‐GPI phenotype was investigated through variance component analysis, and the most significant results were followed up for association with coronary artery disease (CAD) in an independent in silico analysis involving 5765 CAD cases from the PROCARDIS Project and 7264 controls from the PROCARDIS Project and the Wellcome Trust Case Control Consortium (WTCCC) collection. Results After correction for multiple testing, three SNPs located in/around two genes (ELF5 and SCUBE2) reached genome‐wide significance. Moreover, an SNP in the APOH gene showed suggestive association with the β2‐GPI phenotype. Some of the identified genes are plausible biological candidates, as they are actually or potentially involved in inflammatory processes. Conclusions Our results represent a first step towards identifying common variants reflecting the genetic architecture influencing plasma β2‐GPI levels, and warrant further validation by functional experiments, as the functions of some of the discovered loci are still unknown.